Choix du sujet de mémoire par l'étudiant et effets sur la relation pédagogique de direction de mémoire en Master : apprendre à faire le « deuil » du projet de recherche « idéal » - Laetitia Gérard (Université de Provence, 2010)
This article addresses one of the characteristics of the French Master's degree in educational sciences, which makes it different from the Bachelor's degree. Self-directed learning progressively increases in the way the student works, starting with his/her own choice of a research topic. I studied the way the student fits this new role. Semi-directed interviews were carried out with eighteen "supervisor-student" pairs in the discipline of educational sciences, in five different universities. The results show that there is a difference between the initial research that the student would like to lead and the research which is expected at Master's degree. This gap leads to tension within the pedagogical relationship if the student does not accept to let go of his original "ideal" research.